Membangun Kesadaran Masyarakat Di Lingkungan Perkampungan Desa Transisi Kota: Pendekatan Participatory Action Research - Ishaq, Maulana; Mubassir, Ahmad; Arifin, Muhammad Zainul; Saiful, Muhammad; Prasetiya, Benny (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Urban transitional rural villages often face a variety of challenges in areas of village development, such as a lack of awareness of the the importance of being environmentally friendly and limited access to educational resources. This research explores the application of a Participatory Action Research (PAR) approach in building community awareness in an urban transition villagewhich faces significant challenges due to limited educated communities. By involving the community in every stage of the research, from the problem identification to intervention evaluation, PAR serves to create sustainable change and increase community engagement. The research showed that the gap between the village policy system and the community needs as well as systemic barriers, such as resource limitations and resistance to change, are often and resistance to change, often hinder access to and the quality of development of community development. The PAR approach enables the adjustment of village policies, the improvement of skills of village officials, and the development of more responsive community-based policies. community policies that are more responsive. These findings emphasize the importance of active collaboration in research collaboration in research to address unique community issues in transitional environments and recommends further study and action transitional environments and recommend further study and practical to increase awareness, community engagement and local government local government in the community.